Ethanol production capability of Candida shehatae in mixed sugars and rice straw hydrolysate - Prawphan Yuvadetkun,; Mallika Boonmee, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Ethanol fermentations by Candida shehatae TISTR 5843 at low (20 g/L) and high (80 g/L) sugar concentrations with various glucose to xylose ratios were investigated. Glucose was a preferred substrate as it was consumed first at a faster consumption rate. The type of sugar and ratio between glucose and xylose did not have an effect on ethanol produced. The average ethanol concentrations were 7.99 g/L when using 20 g/L sugar and 27.82 g/L when using 80 g/L sugar. Small amounts of xylitol and glycerol as by-products were presented when using 20 g/L sugar. Xylitol appeared to be the main by-product at high xylose concentration with elevated concentrations as xylose is increased. When using rice straw hydrolysate containing 34.75 g/L glucose and 21.29 g/L xylose, 19.37 g/L ethanol was produced with the ethanol yield and ethanol productivity at 0.49 g/g and 0.20 g/L.h, respectively. However, xylose was not completely consumed after fermentation was complete.